ANALISIS KOMODITAS UNGGULAN SUB SEKTOR PETERNAKAN KABUPATEN AGAM TAHUN 2013-2017 - Muthmainnah Istiqadinalova Halibrata; yurni suasti (JURNAL BUANA, 2020)
Abstract The purpose of this research is to determine the superrior commodities of agricultural sector in Agam Regency year 2013-2017. The commodities wich were to be determined in this study consisted of food crops, vegetables, medicinal plants, fruits, estate crops, livestocks, and fisheries. Type of this research was quantitative research using secondary data analysis. The secondary data were obtained from online and printed publications issued by Central Bureau of Statistic of Agam Regency. And analytical method used was descriptive quantitative method with Location Quotient (LQ) analysis tool. Based on the result of this research conclude that commodities which have the highest value in each sub-sector are green bean (LQ=11,27) in Tanjung Mutiara Sub-distric, mustard green (LQ=10,46) in Sungai Puar Sub-distric, Temulawak (LQ=9,79) ini Baso Sub-distric, banana (LQ=4,77) in IV Koto Sub-distric, Gambir (LQ=37) in Palupuh Sub-distric, Quail (LQ=5,21) in Banuhampu Sub-distric, and Marine Fish (LQ=9,13) ini Tanjung Mutiara Sub-distric. Key words: Agricultural Sector, Superrior commodities, Location Quotient